(untitled) (Research, Society and Development, 2022)
Objective: Review of factors described in the literature that are associated with the quality of life of transgender people. Methodology: Integrative review study conducted on the Virtual Health Library platform with a search considering the entire collection using the descriptors "Quality of Life", "Transexual" and "Gender Identity" in combination with keywords and Boolean operators AND and OR. Articles published between 2011 and 2021 were considered. Results: 187 articles were found from the keywords, 161 were eliminated considering the inclusion criteria, 18 articles were eligible. Most of the studies were developed in the US in 2018, taken from Medline and were cross-sectional observational studies of a male and female trans population. Of the studies evaluated, 66.6% performed surgical or hormonal intervention in their sample, and they attribute this intervention as a factor associated with improved quality of life. Other studies have found that different gender identities and sexual orientation, as well as the presence of transexuality, are important factors for a worse or better quality of life. Conclusion: It is possible to distinguish the importance of physical adjustment through surgical or hormonal means in the quality of life of transexual adults. However, there are differences in quality of life and body perception among those evaluated with different gender identities and sexual orientation. There was a lack of quality of life assessment tools aimed at transgender people.